Differential attenuation in star-forming galaxies at 0.3 ≲ z ≲ 1.5 in the SHARDS/CANDELS field. Issue 2 (10th December 2021) - Rodríguez-Muñoz, L; Rodighiero, G; Pérez-González, P G; Talia, M; Baronchelli, I; Morselli, L; Renzini, A; Puglisi, A; Grazian, A; Zanella, A; Mancini, C; Feltre, A; et al.
ABSTRACT: We use a sample of 706 galaxies, selected as [O ii ]λ3727 ([O ii ]) emitters in the Survey for High- z Absorption Red and Dead Sources (SHARDS) on the CANDELS/GOODS-N field, to study the differential attenuation of the nebular emission with respect to the stellar continuum. The sample includes only galaxies with a counterpart in the infrared and log10 ( M * /M⊙ ) > 9, over the redshift interval 0.3 ≲ z ≲ 1.5. Our methodology consists in the comparison of the star formation rates inferred from [O ii ] and Hα emission lines with a robust quantification of the total star-forming activity (SFR TOT ) that is independently estimated based on both infrared and ultraviolet (UV) luminosities. We obtain $f\, =\, E(B-V)_{stellar}$ / E ( B − V )nebular = 0.69$^{0.71}_{0.69}$ and 0.55$^{0.56}_{0.53}$ for [O ii ] and Hα, respectively. Our resulting f -factors display a significant positive correlation with the UV attenuation and shallower or not-significant trends with the stellar mass, the SFRTOT, the distance to the main sequence, and the redshift. Finally, our results favour an average nebular attenuation curve similar in shape to the typical dust curve of local starbursts.